Factors Affecting Bureaucratic Information and Skills of Farmers; the Case of Tokat Province - Gungor Karakas; Esen Oruç; Esra Duran (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study is to determine the factors that affect the development of bureaucratic knowledge and skills of farmers in rural areas. To achieve this aim, a questionnaire was administered face-to-face to 110 farmers. The survey was conducted in the central villages of Tokat Province in 2013. Exploratory factor analysis and confirmatory factor analysis were used to determine the factors that affect the development of farmers’ knowledge and skills regarding bureaucratic procedures. The exploratory factor analysis generated a structure with 4 factors and 10 variables. These factors which explained 76.063% of the total variance, and their reliability coefficients were determined as cooperation tendency (0.803), bureaucratic procedure experience (0.701), level of benefit from government support (0.900) and immediate environment communication (0.601). According to the results of the confirmatory factor analysis, the fit index values were 0.938 for GFI; 0.934 for CFI and 0.913 for NFI. The fact that the RMSEA and CMIN/DF coefficients were also consistent and significant indicates that the results fit the theory. The fact that the intended goodness-of-fit index values of these coefficients were significant also indicates that the results fit the theory. Thus, the factors that affect the bureaucratic knowledge and skills of farmers in the rural areas of Tokat Province were found to be: getting involved in agricultural organizations, the experience of performing formal procedures in public offices, attempts to benefit from agricultural support and immediate environment communication.